TEOLOGI PEMBEBASAN PEREMPUAN DALAM ISLAM - Luthfi Maulana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
This study aims to understand the theology of liberation as an alternative solution that freed because of the discrimination against women. Discrimination against women is a result of the hegemony of patriarchal society jahiliya that is still growing in the view of Islam, so that religion can not function as a mercy to entire human race. Religion as the foundation of justice also become invisible. That condition requires a liberating theology, so it can be used as an alternative to achieve maslaha of the people, including women